Anesthetic Considerations in a Case With Massive Recurrent Clivus Chordoma - Soltanpour, Pardis; Behnaz, Faranak; Azizi Faresani, Hamidreza; Seddighi, Afsoun; Karimian, Maede (International Clinical Neuroscience Journal, 2019)
Chordomas rare low grade slow-growing malignant tumors with an incidence rate of 1 in 100 000 individuals.32% of chordomas occur in the clivus. Diagnosing Clival chordomas could be challenging due to their rare prevalence, insidious onset, and tendency to involve anywhere throughout the craniospinal column. Treating these tumors can also present as a challenge due to their proximity to vital structures and high recurrence rate. We present a case of massive recurrent Clival chordoma in a 27-year-old patient and discuss the anesthetic considerations in such cases.